Steroids In caRdiac Surgery (SIRS) trial: acute kidney injury substudy protocol of an international randomised controlled trial - Michael Walsh; Salim Yusuf; Chirag Parikh; Jessica Vincent; P J Devereaux; Francois Lamontagne; Matthew T V Chan; Richard Whitlock; Meaghan Cuerden; Amit X Garg; Andre Lamy; Daniel I Sessler; et al. (BMJ Open)
Introduction Steroids In caRdiac Surgery trial (SIRS) is a large international randomised controlled trial of methylprednisolone or placebo in patients undergoing cardiac surgery with the use of a cardiopulmonary bypass pump. At the time of surgery, compared with placebo, methylprednisolone divided into two intravenous doses of 250 mg each may reduce the risk of postoperative acute kidney injury (AKI).Methods and analysis With respect to the study schedule, over 7000 substudy eligible patients from 81 centres in 18 countries were randomised in December 2013. The authors will use a logistic regression to estimate the adjusted OR of methylprednisolone versus placebo on the primary outcome of AKI in the 14 days following surgery (a postoperative increase in serum creatinine of ≥50%, or ≥26.5 μmol/L, from the preoperative value). The stage of AKI will also be considered, as will the outcome of AKI in those with and without preoperative chronic kidney disease. After receipt of grant funding, the authors began to record additional perioperative serum creatinine measurements in consecutive patients enrolled at substudy participating centres, and patients were invited to enroll in a 6-month serum creatinine collection. In these trial subpopulations, the authors will consider the outcome of AKI defined in alternate ways, and the outcome of a 6-month change in kidney function from the preoperative value.Ethics and dissemination The authors were competitively awarded a grant from the Canadian Institutes of Health Research for this SIRS AKI substudy. Ethics approval was obtained for additional serum creatinine recordings in consecutive patients enrolled at participating centres. The additional kidney data collection first began for patients enrolled after 1 March 2012. In patients who provided consent, the last 6-month kidney outcome data will be collected in 2014. The results will be reported no later than 2015.Clinical Trial Registration Number NCT00427388.